2020
DOI: 10.1590/1980-5373-mr-2019-0255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treatment of Polyamide Fabric Surface by Hybrid Corona-Dielectric Barrier Discharge: Material Characterization and Dyeing/Washing Processes

Abstract: In this study, the hybrid corona-dielectric barrier discharge plasma treatment was employed to modify the physical, chemical and morphological characteristics of a half-knitted fabric composed of 92% polyamide 6.6 and 8% elastane (PA). These properties of the fabric were evaluated by the water contact angle, x-ray diffraction, infrared spectroscopy, scanning electron microscopy and atomic force microscopy techniques. In addition, the dyeing and washing processes were also investigated. A significant reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…An increase in the peak intensities for argon–oxygen plasma treated nanofibers can be attributed to the presence of bigger crystallites or an increase in the crystallinity fraction. In agreement to our results, two research groups recently reported appearance of new peaks in the XRD spectra of polyamide fibers after plasma activation [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 93%
“…An increase in the peak intensities for argon–oxygen plasma treated nanofibers can be attributed to the presence of bigger crystallites or an increase in the crystallinity fraction. In agreement to our results, two research groups recently reported appearance of new peaks in the XRD spectra of polyamide fibers after plasma activation [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 93%
“…Pristine half-knitted fabric composed of 92% polyamide 6.6 (PA6.6, Rhodia Solvay Group, Santo André, Brazil) and 8% elastane (Lycra brand, Invista, São Paulo, Brazil) was used in this work. This knitted fabric was produced in fine machinery (38 needles per inch) with a surface mass of 180 g/m 2 [ 27 ]. The fabrics were cut into 10 × 8 cm 2 pieces and then washed with a 1% non-ionic detergent solution at room temperature for 30 min and rinsed with water for 10 min to avoid contamination.…”
Section: Methodsmentioning
confidence: 99%
“…To call it a structural change would be a misnomer since it involves the production of functional groups on a cloth fabric surface when the active species, such as free radicals generated by the air ionization, react with atoms or molecules there. This process is often researched in textile surface treatment methods [ 24 , 59 ] and usually does not result in any perceptible structural changes in the fabric, but rather in their functional properties, such as non-wrinkling or fire retardation. These functional groups can be detected via Fourier transform infrared (FTIR) spectroscopy through comparison between two identical fabric samples, one of which is untreated and the other is treated.…”
Section: Characterizationmentioning
confidence: 99%
“…Whereas CDT and its close relative plasma treatment are used to treat knitted or woven cloth fabrics to improve dye retention, flame resistance, etc. [24][25][26][27][28][29][30], applying CDT to electrocharge knitted cloth fabrics has not been reported to our knowledge. On the other hand, non-woven polymer electret fabrics are routinely treated with corona discharge to improve their electrocharging characteristics [31,32].…”
Section: Introductionmentioning
confidence: 99%